Self-Directed Learning Readiness Affects Academic Achievement of Medical Students - Ramdani Firmansyah Hamid; Lutfi Rachman; Marindra Firmansyah (Dinasti International Journal of Education Management And Social Science, 2025)
Students' willingness and desire to learn have an impact on their academic achievement. Students' willingness and desire to learn can be measured by Self-Directed Learning Readiness. However, the relationship between SDLR and academic achievement of medical students has never been studied, so it needs to be done. Descriptive analytical research with a cross-sectional approach was conducted on students (n=184) who met the respondent inclusion criteria. Self-Directed Learning Readiness consists of self-management, self-control, and desire to learn. Self-Directed Learning Readiness ability was measured using the Self-Directed Learning Readiness Scale questionnaire. The academic achievements used in this study were the Objective Structured Clinical Examination scores, Weekly Exams, and Final Block Exams in the Emergency Medicine Block and the Endocrine System Pathology, Metabolism, and Nutrition Block for the 2024/2025 academic year. None of the UNISMA Faculty of Medicine students had low Self-Directed Learning Readiness (high = 126, medium = 58) and there was a significant relationship with the Weekly Exam scores (p = 0.003), Final Block Exam (p = 0.004), and Objective Structured Clinical Examination (p = 0.008). Students with high Self-Directed Learning Readiness showed better academic achievement, especially on the Objective Structured Clinical Examination score (mean = 62.53). There were significant differences between the high, medium, and low Self-Directed Learning Readiness groups on the Weekly Exam scores (p = 0.003), End of Block Exam (p = 0.004), and Objective Structured Clinical Examination (p = 0.008). The test also showed that self-management (p = 0.000, t = 4.862), self-control (p = 0.000, t = 3.507), and learning desire (p = 0.001, t = 3.336) had a significant positive effect on academic achievement. These results indicate the importance of readiness for independent learning in achieving academic success, as well as providing direction for institutions to continue developing students' SDLR. Self-Directed Learning Readiness abilities consisting of self-management, self-control, and desire to learn have a positive and significant effect on the academic achievement of students of the Medical Education Study Program, FK Unisma.